Identification on seed associated mycoflora of sesame genotypes: Identification on seed associated mycoflora of sesame genotypes - K N GUPTA; BURRI RACHEL; RAJANI BISEN (Journal of Oilseeds Research, 2023)
Seed mycoflora of 165 genotypes of sesame in (AVTs & IVTs) were detected using seed health testing methods viz., paper towel method, standard blotter method, and standard agar plate method and six distinct fungi viz.,Alternaria, Macrophomina, Fusarium, Aspergillus, Penicillium, and Rhizopus spp. were detected. In the three methods employed to identify seed mycoflora the standard blotter method has identified the maximum number of seeds infected by fungi compared to paper towel method and standard agar plate method. After a few days of germination, it was observed that the majority of the seeds were infected with disease, which hampered normal seedling growth and resulted in abnormal and rotted seedlings.